ACADEMIC PERSISTENCE AT COMPLETION OF A VENEZUELAN UNIVERSITY LEVELING PROGRAM: SIMÓN BOLÍVAR UNIVERSITY CASE - Arias-Gómez, Diana (2017)
This research was aimed at determining to what extent factors prior to university admission, motivational factors, and institutional experiences explain the academic persistence of students in the University Leveling Term (CIU) at the Simon Bolivar University - Coastal Campus. An explanatory-type quantitative study was proposed, which involved a non-experimental cross-sectional retrospective causal relationship design. The sample consisted of 101 students (50.5% female) with an average age of 17.90 years (SD = 2.37). The study found a significant relationship between some variables explaining academic persistence, which were: a) having a lower orientation toward academic goals; b) a higher score on the maladaptive pattern; c) a higher score in the perception of the Mathematics professor’s evaluation; and d) a higher score in the final performance. This set of variables explains 56.4% of the academic persistence in the CIU program for the study sample. Based on results, this research posits a possible explanation for the academic persistence and analyzes the importance of comparing findings with new research works in different academic settings.